Metal‐Based Nanocatalysts: Metal‐Based Nanocatalysts via a Universal Design on Cellular Structure (Adv. Sci. 3/2020). Issue 3 (5th February 2020) - Zhao, Yajing; Min, Xin; Ding, Zhengping; Chen, Shuang; Ai, Changzhi; Liu, Zhenglian; Yang, Tianzi; Wu, Xiaowen; Liu, Yan'gai; Lin, Shiwei; Huang, Zhaohui; Gao, Peng; et al.
Abstract : In article number 1902051, Xin Min, Shiwei Lin, Peng Gao, Hui Wu, Minghao Fang, and co‐workers prepare a series of metal‐based nanocatalysts through a universal design based on the structure and composition of cell walls and membranes. After an in‐situ carbonization co‐reduction process, these metal nanoparticles, including Pt, Ru, Rh, Pd, Ag, Ir, Au, Co and Ni, uniformly and stably bond with N‐doped carbon support, which exhibits an excellent catalytic activity for the hydrogen evolution reaction.